2017
DOI: 10.1007/s40262-017-0605-6
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Upadacitinib in Healthy Subjects and Subjects with Rheumatoid Arthritis: Analyses of Phase I and II Clinical Trials

Abstract: Background and ObjectivesUpadacitinib is a janus kinase (JAK) 1 inhibitor being developed for the treatment of rheumatoid arthritis (RA) and other inflammatory diseases. This work characterized upadacitinib population pharmacokinetics in healthy subjects and RA patients and the effects of covariates on upadacitinib exposure.MethodsUpadacitinib plasma concentrations (n = 6399) from 107 healthy subjects and 466 RA patients from three phase I and two 12-week RA phase IIb trials (1–48 mg immediate-release doses ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
87
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 15 publications
(23 reference statements)
8
87
0
1
Order By: Relevance
“…The ER formulation of upadacitinib was developed to enable once‐daily dosing in phase 3 studies. Upadacitinib plasma exposure was approximately dose proportional and time independent over the range of IR and ER doses evaluated in clinical studies . The bioavailability of the ER formulation used in this study as well as in phase 3 studies is 76% relative to the IR formulation .…”
mentioning
confidence: 80%
“…The ER formulation of upadacitinib was developed to enable once‐daily dosing in phase 3 studies. Upadacitinib plasma exposure was approximately dose proportional and time independent over the range of IR and ER doses evaluated in clinical studies . The bioavailability of the ER formulation used in this study as well as in phase 3 studies is 76% relative to the IR formulation .…”
mentioning
confidence: 80%
“…However, given that renal elimination plays a minor role in upadacitinib elimination, hemodialysis is not expected to have a clinically relevant effect on upadacitinib plasma exposures . In subjects with RA, upadacitinib CL/F for the immediate‐release formulation is estimated to be 30.2 L/h (503 mL/min) . Based on a percentage of upadacitinib immediate‐release dose eliminated in the urine of approximately 20%, upadacitinib nonrenal clearance is estimated to be approximately 400 mL/min (assuming 100% bioavailability for the immediate‐release formulation).…”
Section: Discussionmentioning
confidence: 99%
“…Upadacitinib pharmacokinetics were characterized in healthy subjects following the administration of a range of immediate‐release (1 mg to 48 mg) and extended‐release (7.5 mg to 45 mg [including data on file, AbbVie]) doses . Upadacitinib plasma exposures were approximately dose‐proportional over the range of immediate‐release or extended‐release doses evaluated in clinical studies . Approximately 20% of upadacitinib immediate‐release dose is eliminated in urine as unchanged upadacitinib .…”
mentioning
confidence: 99%
“…There was no significant accumulation of upadacitinib in plasma with twice-daily dosing of the IR formulation, and approximately 20% of the upadacitinib dose was eliminated unchanged in urine. 12 Intersubject variability in healthy subjects and subjects with rheumatoid arthritis (RA) was estimated to be 16% and 26%, respectively, for apparent upadacitinib oral clearance and 14% and 27%, respectively, for upadacitinib apparent central volume of distribution. Administration of the strong CYP3A inhibitor ketoconazole resulted in a 75% increase in upadacitinib AUC, whereas the CYP inducer rifampin decreased upadacitinib AUC by 60%.…”
mentioning
confidence: 99%
“…10 Upadacitinib is a nonsensitive substrate for cytochrome P450 (CYP) 3A with a minor contribution of CYP2D6 in vitro. 12 Two dose-ranging phase 2 studies evaluated the efficacy and safety of upadacitinib in subjects with RA who had inadequate response to methotrexate or anti-tumor necrosis factor therapy. 11 In a population pharmacokinetic analysis of phase 1 and 2 studies, the CYP2D6 metabolic phenotype showed no effect on the apparent upadacitinib oral clearance; mild and moderate renal impairment was estimated to result in 16% and 32% higher upadacitinib AUC compared with subjects with normal renal function.…”
mentioning
confidence: 99%